2021
DOI: 10.1186/s12891-021-03969-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary clear cell sarcoma of the femur: a unique case with RT-PCR and direct sequencing confirmation of EWSR1/ATF1 fusion gene

Abstract: Background It is very rare for clear cell sarcomas (CCS) to arise in the bone. During diagnosis, it is important to distinguish primary CCS of bone from bone metastasis of melanoma because this difference fundamentally changes the therapeutic options. Recently, characteristic fusion genes of CCS have been detected using reverse transcription polymerase chain reaction (RT-PCR) or direct sequencing which allowed to distinguish CCS from melanoma. However, there was no study applying these analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Ten of 14 cases identified upon literature review either demonstrated negative FISH for EWSR1 rearrangement (4 cases) 26,27,30,31 or the testing was not performed or reported (6 cases). 22,24,29,[32][33][34] In 4 cases (Table 2), 21,23,25,28 the pathognomonic rearrangement was demonstrated either by FISH (2 cases), RT-PCR (1 case), or by an undescribed method (1 case). One of these tumors was negative for HMB-45 and melan A (a rare occurrence for CCS) 25 ; without confirmation of the fusion partner, it is difficult to be entirely certain that the diagnosis was correct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten of 14 cases identified upon literature review either demonstrated negative FISH for EWSR1 rearrangement (4 cases) 26,27,30,31 or the testing was not performed or reported (6 cases). 22,24,29,[32][33][34] In 4 cases (Table 2), 21,23,25,28 the pathognomonic rearrangement was demonstrated either by FISH (2 cases), RT-PCR (1 case), or by an undescribed method (1 case). One of these tumors was negative for HMB-45 and melan A (a rare occurrence for CCS) 25 ; without confirmation of the fusion partner, it is difficult to be entirely certain that the diagnosis was correct.…”
Section: Discussionmentioning
confidence: 99%
“…While characteristic clinicopathologic characteristics of CCS (young patient age, predilection for tendons and aponeuroses of distal extremities, and uniform cytomorphology) can help suggest the diagnosis, rare presentations are particularly problematic and can easily lead to misdiagnosis as metastatic melanoma. One such circumstance is represented by primary bone presentation of CCS, previously reported as rare cases 21–34. Here, we report a series of primary bone CCS.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) showed a bone tumor. An open biopsy was performed, and reverse transcription-polymerase chain reaction (RT-PCR) and direct sequencing revealed the EWSR1 / ATF1 fusion gene in the tumor specimens[ 14 ]. No other signs of metastasis were found on whole-body CT and positron emission tomography/CT.…”
Section: Case Presentationmentioning
confidence: 99%